2004
DOI: 10.1002/qua.20193
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical study of alternating N/B and N/C π bonds in (un)charged even‐membered 4n and 4n+2 cyclic systems and their related open systems

Abstract: ABSTRACT:With semi-empirical MO and ab initio calculations at different levels, we investigated the conjugation of alternating XOY bonds with XOY for N/B and N/C combinations in an open and cyclic arrangement. Although the intrinsic symmetry is lost for the acyclic even-membered compounds, the alternation is still reflected in its geometry and electron-density transfer. For the cyclic compounds, we focused our attention on borazine N 3 B 3 H 6 (D 3h symmetry), which is isoelectronic with benzene (D 6h symmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Methyl transfer from H 3 CFCH 3+ has been studied under gas‐phase FT‐ICR experiments with borazine (B 3 N 3 H 6 , the inorganic analogue of benzene). A highly efficient methyl transfer from H 3 CFCH 3+ yields [B 3 N 3 H 6 + CH 3+], the ionic intermediate of N ‐methylborazine26, 27. The other dimethylhalonium ions have been studied with gas‐phase MS experiments using pyridine as methyl acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl transfer from H 3 CFCH 3+ has been studied under gas‐phase FT‐ICR experiments with borazine (B 3 N 3 H 6 , the inorganic analogue of benzene). A highly efficient methyl transfer from H 3 CFCH 3+ yields [B 3 N 3 H 6 + CH 3+], the ionic intermediate of N ‐methylborazine26, 27. The other dimethylhalonium ions have been studied with gas‐phase MS experiments using pyridine as methyl acceptor.…”
Section: Resultsmentioning
confidence: 99%
“…For our studies, we have subdivided B−N compounds into several classes: amineboranes H 3 B·NH 3 (the analogue of ethane) and its derivatives; aminoboranes H 2 BNH 2 (the analogue of ethylene) and its derivatives; iminoboranes HB⋮NH (the analogue of acetylene) and its derivatives; borazine B 3 N 3 H 6 (the analogue of benzene) and its derivatives; boron nitride (hexagonal and cubic, the analogues of graphite and diamond). The structures and bonding properties of borazine have been investigated by many other groups. In particular, recent density functional studies of borazine and some of its derivatives have been reported by Miao and co-workers 12 and Rahaman and co-workers, with the aim of quantifying the aromaticity of this molecule. Although these investigators computed chemical shifts for these molecules, they did not compute coupling constants.…”
Section: Introductionmentioning
confidence: 99%
“…This is in excellent agreement with the result that charge accommodation at chlorine is much more favored than at fluorine. In this respect, it is of interest to note that (CH 3 ) 2 F + , in contrast to the other dimethyl halonium ions, does not exist in solution 27, 28. With these results, it is possible to put forward that hydrogen bridging via a presumable solvated proton of the acid or dipolar interactions via neighboring (solvent) effects with the halogens may favor a geometric change into a TP geometry.…”
Section: Resultsmentioning
confidence: 99%